Comparison of 4 questionnaires for assessment of fruit and vegetable intake - Field, A E; Colditz, G A; Fox, M K; Byers, T; Serdula, M; Bosch, R J; Peterson, K E (American journal of public health (1971), 1998)
OBJECTIVE: This study compared fruit and vegetable assessments derived from 4 self-administered questionnaires. METHODS: Among 102 adolescents, servings of fruits and vegetables assessed by 4 questionnaires were compared with estimates from 24-hour recalls. RESULTS: The prevalence of consuming 5 or more servings of fruits and vegetables a day was underestimated by the questionnaires. Questionnaires asking subjects to recall their diet over the previous year were more effective in ranking subjects (r's > or = .42) than those assessing previous-day diet (r's > or = .30). CONCLUSIONS: Brief assessments of fruit and vegetable intake are more useful for ranking subjects than for estimating prevalence of consumption of 5 or more servings per day.